2020
DOI: 10.3233/thc-192024
|View full text |Cite
|
Sign up to set email alerts
|

Using a filming protocol to improve video-instructed cardiopulmonary resuscitation

Abstract: BACKGROUND: Video communications during cardiopulmonary resuscitation (CPR) can improve the quality of information exchange between a bystander performing CPR and an emergency medical dispatcher (EMD). OBJECTIVE: To improve chest compression effectiveness, a filming protocol instructing video camera placements around a patient was developed. This study measured whether the filming protocol increased chest compressions' effectiveness. METHODS: A simulation study was conducted comparing CPR effectiveness under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…We also identified 13 manikin simulation studies that compared video-based with audio-based dispatch. 4–16 The simulation studies showed improved CPR quality parameters such as compression rate and time to compression in the video-based dispatch group but did not show any significant differences in chest compression depth, correct compression depth, correct hand position, correct chest release, or time to defibrillation.…”
Section: Basic Life Supportmentioning
confidence: 96%
“…We also identified 13 manikin simulation studies that compared video-based with audio-based dispatch. 4–16 The simulation studies showed improved CPR quality parameters such as compression rate and time to compression in the video-based dispatch group but did not show any significant differences in chest compression depth, correct compression depth, correct hand position, correct chest release, or time to defibrillation.…”
Section: Basic Life Supportmentioning
confidence: 96%
“…13 Furthermore, the dispatcher must be prepared not only for the added value of the image in improving situational awareness, but also trained for the psychological effects of sometimes unpleasant or disturbing visual perceptions. In addition, dispatchers will need to be able to recommend the best way and angle or perspective to capture the whole situation most effectively on camera and to be prepared to deal with the various quality of video image transfer under different ambient conditions, [40][41][42] as well as solve issues prioritizing filming instead of helping the patient. 43 Such a protocol should be proposed and implemented with a prospective analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have predominantly focused on out-of-hospital cardiac arrest, with evidence of clinical benefit in this setting [ 9 , 10 ]. Most of these studies have been simulation-based [ 11 13 ] with few studies in real-life settings. Evidence suggests that use of video livestreaming from the scene may impact on decision-making [ 8 , 14 ] and enable faster and more accurate decisions about EMS resources to be tasked [ 3 ].…”
Section: Introductionmentioning
confidence: 99%